2009
DOI: 10.1007/s10802-009-9372-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic Traits in Youth: Is There Evidence for Primary and Secondary Subtypes?

Abstract: The current study employed model-based cluster analysis in a sample of male adolescent offenders (n = 94) to examine subtypes based on psychopathic traits and anxiety. Using the Psychopathy Checklist: Youth Version (PCL:YV; Forth et al. 2003) and the self-report Antisocial Process Screening Device (APSD; Caputo et al. 1999), analyses identified three clusters in males that varied in the severity of psychopathic traits (low, moderate, and high) and anxiety. The high psychopathic group exhibited more negative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 35 publications
(48 reference statements)
12
83
3
1
Order By: Relevance
“…Several research findings have shown, however, that there may be some developmental differences in the concept of psychopathy in childhood, in that studies tend to indicate only modest levels of stability, greater levels of comorbidity (Kubak & Salekin, 2009;Salekin, Leistico, Trobst, Schrum, & Lochman, 2005;Salekin, Neumann, Leistico, DiCicco, & Duros, 2004b), and dissimilar correlates with internalizing symptoms and some performance tasks (see Forth, Kosson, & Hare, 2003;Lee, Salekin, & Iselin, 2010;Salekin, 2006;Salekin & Frick, 2005;Salekin, Rosenbaum, Lee, & Lester, 2009). While it remains unclear to what extent research findings will continue to elucidate similarities and differences in the concept of child psychopathy, scientific findings, as they currently stand, may be encouraging for the treatment of psychopathy in children and adolescents.…”
Section: Hare's Model As a Starting Pointmentioning
confidence: 99%
“…Several research findings have shown, however, that there may be some developmental differences in the concept of psychopathy in childhood, in that studies tend to indicate only modest levels of stability, greater levels of comorbidity (Kubak & Salekin, 2009;Salekin, Leistico, Trobst, Schrum, & Lochman, 2005;Salekin, Neumann, Leistico, DiCicco, & Duros, 2004b), and dissimilar correlates with internalizing symptoms and some performance tasks (see Forth, Kosson, & Hare, 2003;Lee, Salekin, & Iselin, 2010;Salekin, 2006;Salekin & Frick, 2005;Salekin, Rosenbaum, Lee, & Lester, 2009). While it remains unclear to what extent research findings will continue to elucidate similarities and differences in the concept of child psychopathy, scientific findings, as they currently stand, may be encouraging for the treatment of psychopathy in children and adolescents.…”
Section: Hare's Model As a Starting Pointmentioning
confidence: 99%
“…Similar distinctions have been attempted with moderate success in child populations, with primary and secondary groups differing on negative and positive personality traits, respectively (Lee, Salekin & Iselin, 2010). However, difficulties in separating primary and secondary types into homogenous groups have resulted in less than adequate attempts to clarify their underlying etiology (Newman et al, 2005).…”
Section: Psychopathy In Childrenmentioning
confidence: 96%
“…Among children with CU, anxiety has been associated with greater questionnaire-based reports of impulsivity and externalizing behavior problems, as well as higher reports of aggression and delinquency Rosan et al, 2015;Vaughn et al, 2009), especially reactive aggression (Fanti et al, 2013), a more extensive criminal offense record (Kimonis et al, 2011), and increased reports of depressive and psychotic symptoms (Docherty et al, 2015;Vaughn et al, 2009) relative to CU youth without anxiety. These anxiety-related differences hold true despite comparable levels of CU traits, although some studies have noted increased (Kimonis et al, 2011;Lee et al, 2010) or decreased (Euler et al, 2015) CU trait severity among youth who show anxiety symptoms relative to CU youth without anxiety. Anxiety may interact with CU in important ways, but the nature of such interactions and their impact on youth aggressive behavior remain unclear, impeding the identification of tailored treatment targets, and hindering efforts to address the unique needs of children at various points on these continua.…”
Section: Cu and Anxietymentioning
confidence: 96%
“…Empirical work suggests that anxiety-related heterogeneity in youth showing CU traits may be related to meaningful differences in associated aggressive behavior, with the presence of both CU traits and anxiety associated with a specific pattern of emotional processing deficits and higher levels of aggression than children with just CU traits (Docherty, Boxer, Huesmann, O'Brien, & Bushman, 2015;Euler et al, 2015;Fanti, Demetrious, & Kimonis, 2013;Humayun, Kahn, Frick, & Viding, 2014;Kahn et al, 2013;Kimonis, Skeem, Cauffman, & Dmitrieva, 2011;Lee, Salekin, & Iselin, 2010;Rosan, Frick, Gottlieb, & Fasicaru, 2015). However, much of this research has relied exclusively on questionnaire reports of aggressive behavior rather than observed aggressive behavior (e.g., Kimonis et al, 2011;Lee et al, 2010), and has not examined how anxiety and CU traits predict child aggression in the context of experimentally manipulated distress cue salience from potential victims. Much remains to be learned about the processes underlying observed associations between anxiety, CU traits, and aggressive behavior among youth in order to optimally inform taxonomy questions and intervention efforts.…”
Section: List Of Acronyms and Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation